Smartseille, opération pionnière de l’extension d’Euroméditerranée, Marseille : derrière l’innovation, l’expérimentation pour modifier les modes de faire - Brigitte Bertoncello; Zoé Hagel (Territoire en Mouvement)
This article analyzes how to create a city based on Smartseille, a real estate operation that is not attached to existing buildings and the first stone in the extension of Euroméditerranée in Marseille, in a context of large wastelands, in an impoverished neighborhood that is under-equipped. Labelled as an industrial demonstrator for the sustainable city, it is based on a requirement for innovation which the actors have seized as an opportunity for experimentation and the right to make mistakes. This project has become an "already there" in terms of new construction, and has notably contributed to the reference framework currently being developed by Euroméditerranée. Far from the initial idea of a model, its reproducibility moves away from copying and pasting and is built as much on the success of certain innovations as on what did not work. Smartseille is the result of an opportunity urbanism that combines the intentions of a promoter and a developer with the availability of land, and is slow to become part of the city. Behind the concepts, tools and constraints with which the actors deal, the analysis of this operation on which the rest of the project will be based questions the limits of the modes of production and what makes it possible to make a city.